2012
DOI: 10.1016/j.pain.2012.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced affect/cognition-related brain responses during visceral placebo analgesia in irritable bowel syndrome patients

Abstract: Placebo analgesia is a psychosocial context effect that is rarely studied in visceral pain. Patients with irritable bowel syndrome (IBS) exhibit visceral hyperalgesia and heightened affective/cognitive brain region activation during visceral stimuli. Psychological factors alter the pain and brain activation pattern, and these changes are more pronounced in IBS patients. Expectation constitutes the major neuropsychological mechanism in the placebo effect. This study confirmed the heightened affective/cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 45 publications
7
64
0
6
Order By: Relevance
“…In addition, in the "50% condition," the placebo-induced pain relief was more pronounced in those subjects who believed they were in the active-treatment group . A direct comparison in the placebo Neuro-Bio-Behavioral Mechanisms of Placebo and Nocebo Responses response to visceral pain between IBS patients and healthy volunteers demonstrated similar placebo responses at the behavioral level (magnitude of placebo analgesia) but a more pronounced neural response in affective and cognitive brain regions (insula, cingulate cortex, prefrontal cortex), suggesting altered neural processing of placebo-induced changes in pain perception in IBS and in patients with ulcerative colitis in remission (Lee et al, 2012;Schmid et al, 2015).…”
Section: G Gastrointestinal System/irritable Bowel Syndromementioning
confidence: 91%
“…In addition, in the "50% condition," the placebo-induced pain relief was more pronounced in those subjects who believed they were in the active-treatment group . A direct comparison in the placebo Neuro-Bio-Behavioral Mechanisms of Placebo and Nocebo Responses response to visceral pain between IBS patients and healthy volunteers demonstrated similar placebo responses at the behavioral level (magnitude of placebo analgesia) but a more pronounced neural response in affective and cognitive brain regions (insula, cingulate cortex, prefrontal cortex), suggesting altered neural processing of placebo-induced changes in pain perception in IBS and in patients with ulcerative colitis in remission (Lee et al, 2012;Schmid et al, 2015).…”
Section: G Gastrointestinal System/irritable Bowel Syndromementioning
confidence: 91%
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…At the same time, placebo-induced neural modulation during rectal pain differed in patients with IBS as compared with healthy controls, involving multiple brain regions. 93,94 Specifically, in the study by Schmid et al, 93 healthy individuals as well as patients with ulcerative colitis in remission showed reduced activation in pain-related brain areas during placebo analgesia, whereas no changes could be observed in patients with IBS. These differences in neural modulation were most impressive in the cingulate cortex.…”
Section: Nauseamentioning
confidence: 99%